A new photoelectrochemical biosensor based on FeOOH and exonuclease III-aided dual recycling signal amplification for HPV-16 detection. Issue 52 (4th June 2021) - Wang, Yanlin; Xia, Lingying; Xiang, Xuelian; Yuan, Ruo; Wei, Shaping
Abstract : Herein, based on iron oxyhydroxide (FeOOH) as the photoactive material and exonuclease III (exo III)-aided dual recycling signal amplification, a new photoelectrochemical (PEC) biosensor was successfully developed for human papillomavirus-16 (HPV-16) detection. Abstract : Herein, based on iron oxyhydroxide (FeOOH) as the photoactive material and exonuclease III (exo III)-aided dual recycling signal amplification, a new photoelectrochemical (PEC) biosensor was successfully developed for human papillomavirus-16 (HPV-16) detection with a wide linear range from 0.5 fM to 1 nM and a low detection limit of 0.17 fM.